Byron R. White papers - White, Byron R., 1917-2002.
Opinion files and related administrative records documenting cases heard during White's tenure on the U.S. Supreme Court. Opinion files contain memoranda and drafts of majority opinions, dissents, and concurrences; administrative files contain case assignment lists, circulation records, conference lists, schedules of court hearings, decision statistics, per curiam opinions, and docket sheets. Includes records of cases in which White was disqualified and those he requested be discussed in conference. Also includes memoranda and reports by administrative officers of the Supreme Court. Includes material on cases invovling the "Miranda law" (that suspects must be informed of their rights before police questioning), abortion, child pornography, freedom of speech, homosexuality, racial bias, and liability of news organizations.
Associate justice of the U.S. Supreme Court, appointed by President John F. Kennedy in 1962; formerly U.S. deputy attorney general, lawyer, naval intelligence officer, Rhodes scholar, and professional football player. Full name: Byron Raymond White. Nickname: Whizzer.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: United States. -- Supreme Court; Abortion -- United States; Child pornography -- United States; Constitutional law -- United States; Freedom of speech -- United States; Homosexuality -- Law and legislation -- United States; Judicial opinions -- United States; Law -- Cases -- United States; Law -- United States; Police questioning -- United States; Press -- Liability (Law); Racism -- United States; Jurists